Fabrication Of Porous Ceramic Foam As Catalyst Support For Hydrotalcite In The Production Of Fatty Acid Methyl Esters (Fame) - Sharif, Sharmiwati Mohammed (2014)
The increasing demand for liquid petrol fuels, as well as their higher price, biodiesel has been gaining worldwide popularity as an alternative energy source. The classic ways of producing biodiesel have certain difficulties and disadvantages such as that determined researchers for finding alternative technologies for its production. Thus, upgraded technology of biodiesel production has been proposed. The tubular porcelain catalyst as the catalyst support and hydrotalcite as the heterogeneous catalyst were prepared. Analyses have been done including the methods of preparation of the tubular ceramic support with the replication polymeric sponge method, characterization of mechanical and microstructure properties of tubular ceramic support and the application on the transesterification of commercial palm cooking oil to biodiesel. T